Capital Structure Analysis Of Foreign Investment Companies With Domestic Investment Companies In An Effort To Optimize Company Capital Structure - Risma Rahmadani; Dr. Hj. Andi Ratna Sari Dewi, SE, M.Sc (Citakonsultindo, 2023)
This study provides an overview in determining the optimal capital structure that is able to minimize the cost of capital, and then maximize the value of the company. Although from an academic perspective, the issue of whether there is an optimal capital structure is still controversial, from a practical point of view, capital structure has an effect on firm value. Multinational companies have different characteristics from domestic companies, so that the optimal capital structure for the two types of companies is also different. In other words , can multinational companies achieve a more optimal capital structure when compared to domestic companies?